The Role and Responsibilities of the Universities in the Transformation of Anatolian Cities in Turkey - Savas-Yavuzcehre, PÄ±nar (European Scientific Journal, ESJ, 2017)
Although there are many elements that shape cities, universities have been first among these elements in recent years. The main purpose of the universities, which are central to the societal progress, is to conduct scientific research, generate knowledge, combine cultures and provide necessary professional skills. In addition to these objectives, it is expected that the universities in Turkey would also contribute to their host cities in many ways. Today, each Anatolian city has at least one university. This study aims to question the role and responsibilities of the universities in the transformation of Anatolian cities in Turkey. Therefore, the demographical, economical, geographical, industrial, societal and cultural effects of universities on their cities will be discussed in the framework of Turkey. As the results of the study: i) Universities are expected to play a substantial role as an urban development agent especially in terms of demography and economy, ii) The effects of the universities in the cities are felt more in the undeveloped cities than in the developed ones, iii) Universities also affect their cities in terms of the employment structure, housing, health facilities, physical infrastructure, quality of life, societal and cultural structure.